Accelerated Aging and Age-Related Diseases (CVD and Neurological) Due to Air Pollution and Traffic Noise Exposure - Hahad, Omar (Int J Mol Sci, 2021)
The World Health Organization estimates that only approximately 25% of diversity in longevity is explained by genetic factors, while the other 75% is largely determined by interactions with the physical and social environments. Indeed, aging is a multifactorial process that is influenced by a range of environmental, sociodemographic, and biopsychosocial factors, all of which might act in concert to determine the process of aging. The global average life expectancy increased fundamentally over the past century, toward an aging population, correlating with the development and onset of age-related diseases, mainly from cardiovascular and neurological nature. Therefore, the identification of determinants of healthy and unhealthy aging is a major goal to lower the burden and socioeconomic costs of age-related diseases. The role of environmental factors (such as air pollution and noise exposure) as crucial determinants of the aging process are being increasingly recognized. Here, we critically review recent findings concerning the pathomechanisms underlying the aging process and their correlates in cardiovascular and neurological disease, centered on oxidative stress and inflammation, as well as the influence of prominent environmental pollutants, namely air pollution and traffic noise exposure, which is suggested to accelerate the aging process. Insight into these types of relationships and appropriate preventive strategies are urgently needed to promote healthy aging.